Case-Control Study of Drug Monitoring of β-Lactams in Obese Critically Ill Patients - Hites, Maya (American Society for Microbiology, 2013)
Severe sepsis and septic shock can alter the pharmacokinetics of broad-spectrum β-lactams (meropenem, ceftazidime/cefepime, and piperacillin-tazobactam), resulting in inappropriate serum concentrations. Obesity may further modify the pharmacokinetics of these agents. We reviewed our data on critically ill obese patients (body mass index of ≥30 kg/m(2)) treated with a broad-spectrum β-lactam in whom therapeutic drug monitoring was performed and compared the data to those obtained in critically nonobese patients (body mass index of <25 kg/m(2)) to assess whether there were differences in reaching optimal drug concentrations for the treatment of nosocomial infections. Sixty-eight serum levels were obtained from 49 obese patients. There was considerable variability in β-lactam serum concentrations (coefficient of variation of 50% to 92% for the three drugs). Standard drug regimens of β-lactams resulted in insufficient serum concentrations in 32% of the patients and overdosed concentrations in 25%. Continuous renal replacement therapy was identified by multivariable analysis as a risk factor for overdosage and a protective factor for insufficient β-lactam serum concentrations. The serum drug levels from the obese cohort were well matched for age, gender, renal function, and sequential organ failure assessment (SOFA) score to 68 serum levels measured in 59 nonobese patients. The only difference observed between the two cohorts was in the subgroup of patients treated with meropenem and who were not receiving continuous renal replacement therapy: serum concentrations were lower in the obese cohort. No differences were observed in pharmacokinetic variables between the two groups. Routine therapeutic drug monitoring of β-lactams should be continued in obese critically ill patients.